2018
DOI: 10.1161/jaha.117.008508
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcomes of Cardiac Resynchronization Therapy Using Apical Versus Nonapical Left Ventricular Pacing

Abstract: BackgroundExperimental evidence indicates that left ventricular (LV) apical pacing is hemodynamically superior to nonapical LV pacing. Some studies have shown that an LV apical lead position is unfavorable in cardiac resynchronization therapy. We sought to determine whether an apical LV lead position influences cardiac mortality after cardiac resynchronization therapy.Methods and ResultsIn this retrospective observational study, the primary end point of cardiac mortality was assessed in relation to longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…It established the benefit of a CRT over medical therapy in eligible patients, but was underpowered to compare any difference between CRT-P and CRT-D. 7 The majority of comparisons of CRT-P vs. CRT-D have been retrospective cohort studies and these have suggested that the benefit for a CRT-D over a CRT-P may be limited to those patients with ischaemic heart failure aetiology. 20,33,34 The only recent RCT of defibrillator over standard care, the DANISH study, randomized 556 patients with heart failure of non-ischaemic aetiology with an LVEF ≤35% to either receive an ICD or usual clinical care. Despite the rate of sudden cardiac death being half in the ICD group (4.3%) compared with the control group (8.2%) this trial showed no significant difference in overall survival benefit between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…It established the benefit of a CRT over medical therapy in eligible patients, but was underpowered to compare any difference between CRT-P and CRT-D. 7 The majority of comparisons of CRT-P vs. CRT-D have been retrospective cohort studies and these have suggested that the benefit for a CRT-D over a CRT-P may be limited to those patients with ischaemic heart failure aetiology. 20,33,34 The only recent RCT of defibrillator over standard care, the DANISH study, randomized 556 patients with heart failure of non-ischaemic aetiology with an LVEF ≤35% to either receive an ICD or usual clinical care. Despite the rate of sudden cardiac death being half in the ICD group (4.3%) compared with the control group (8.2%) this trial showed no significant difference in overall survival benefit between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that investigated whether a nonapical RV load position, closer to the His-Purkinje system, could improve outcome in CRT found no differences in echocardiographic or clinical endpoints as opposed to a conventional RV lead positon. 21 However, paced effects (eg, interlead delays)…”
Section: Fallacy Of Empirical Lead Placement In Crt Rv Lead Position and Lv-only Pacingmentioning
confidence: 99%
“…26 Optimal LV pacing site is patient-specific Accumulated evidence in over 4200 patients from various landmark trials taught us that, on the group level, no single site is consistently superior (or inferior) to another with respect to long-term outcome. 21,27,28 Conversely, the interand intraindividual heterogeneity of the optimal LV pacing site becomes apparent in many interventional studies in which AHB was systematically explored during BVP at various sites. Pacing a suboptimal site improves the maximum rate of LV pressure rise (dP/dt max ) on average by 613%.…”
Section: Fallacy Of Empirical Lead Placement In Crt Rv Lead Position and Lv-only Pacingmentioning
confidence: 99%
See 2 more Smart Citations